Evaluasi Usability Aplikasi Workin dengan Metode SUS (System Usability Scale) - Sugiana, I Wayan; Widiartha, S.Si., M.Kom., I Made (Jurnal Nasional Teknologi Informasi dan Aplikasnya; Vol 1 No 1 (2022): JNATIA Vol. 1, No. 1, November 2022, 2022)
To measure usability of an app we can use many methods. One of them is SUS (System Usability Scale). This method provides a “quick and dirty”, reliable tool for measuring the usability. So in this paper the writer uses this method to measure usability of a prototype of an app named “Workin”. Workin is a mobile app that helps the user to manage their work. There are features such as work data statistics, timer, write down task, and reminder. The writer creates the prototype using Figma and uses Google Form to share the questioner that contains questions used on SUS (System Usability Scale) method to get the usability measure of the Workin App. The result from the questioner then calculated using a calculation that is available at SUS (System Usability Scale) method.